PENGARUH DEBT TO EQUITY RATIO DAN NET PROFIT MARGIN TERHADAP RETURN ON EQUITY RATIO (STUDI PADA PERUSAHAAN GO PUBLIC SEKTOR PROPERTI, REAL ESTATE DAN KONSTRUKSI YANG TERDAFTAR DI BEI PERIODE 2017-2019) - Febriana Dwika Putri; I Wayan Sukadana; I Wayan Suarjana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
This study aims to determine the effect of Debt to Equity Ratio (DER) and Net Profit Margin (NPM) on Return on Equity Ratio (ROE) in publicly listed companies in the property, real estate and construction sectors listed on the Indonesia Stock Exchange (IDX) for the 2017 period. -2019. The sample in this study were 10 property, real estate and construction companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. Determination of the sample using purposive sampling method. The analytical tool used is multiple regression analysis and hypothesis testing using t-test partially, F-test simultaneously with a level of significance of 5%. The results of the research to test the effect indicate that the variable Debt to Equity Ratio (DER) does not significantly affect the Return on Equity Ratio (ROE), the variable Net Profit Margin (NPM) has a significant positive effect on the Return on Equity Ratio (ROE) and the variable Debt to Equity Ratio (ROE). Equity Ratio (DER) and Net Profit Margin (NPM) have a significant effect on the Return on Equity Ratio (ROE) in property, real estate and construction companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period.